A method to quantify and value floodplain sediment and nutrient retention ecosystem services. (15th August 2018) - Hopkins, Kristina G.; Noe, Gregory B.; Franco, Fabiano; Pindilli, Emily J.; Gordon, Stephanie; Metes, Marina J.; Claggett, Peter R.; Gellis, Allen C.; Hupp, Cliff R.; Hogan, Dianna M.
Abstract: Floodplains provide critical ecosystem services to local and downstream communities by retaining floodwaters, sediments, and nutrients. The dynamic nature of floodplains is such that these areas can both accumulate sediment and nutrients through deposition, and export material downstream through erosion. Therefore, estimating floodplain sediment and nutrient retention should consider the net flux of both depositional and erosive processes. An ecosystem services framework was used to quantify and value the sediment and nutrient ecosystem service provided by floodplains in the Difficult Run watershed, a small (151 km 2 ) suburban watershed located in the Piedmont of Virginia (USA). A sediment balance was developed for Difficult Run and two nested watersheds. The balance included upland sediment delivery to streams, stream bank flux, floodplain flux, and stream load. Upland sediment delivery was estimated using geospatial datasets and a modified Revised Universal Soil Loss Equation. Predictive models were developed to extrapolate field measurements of the flux of sediment, sediment-bound nitrogen (N), and sediment-bound phosphorus (P) from stream banks and floodplains to 3232 delineated stream segments in the study area. A replacement cost approach was used to estimate the economic value of the sediment and nutrient retention ecosystem service based on estimated net stream bank and floodplain flux of sediment-bound N for all streams in the study area. Results indicated the net fluvial fluxes of sediment, sediment-bound N, and sediment-bound P were −10, 439 Mg yr −1 (net export), 57, 300 kg-N yr −1 (net trapping), and 98 kg-P yr −1 (net trapping), respectively. For sediment, floodplain retention was offset by substantial losses from stream bank erosion, particularly in headwater catchments, resulting in a net export of sediment. Nutrient retention in the floodplain exceeded that lost through stream bank erosion resulting in net retention of nutrients (TN and TP). Using a conservative cost estimate of $12.69 (USD) per kilogram of nitrogen, derived from wastewater treatment costs, the estimated annual value for sediment and nutrient retention on Difficult Run floodplains was $727, 226 ± 194, 220 USD/yr. Values and differences in floodplain nitrogen retention among stream reaches can be used to target areas for floodplain conservation and stream restoration. The methods presented are scalable and transferable to other areas if appropriate datasets are available for validation. Highlights: This study combines field and geospatial data to estimate floodplain sediment and nutrient fluxes and their economic value. N and P retention on the floodplain exceeded losses through bank erosion. Floodplain nitrogen retention had a replacement value of 12.69 USD per kg based on wastewater treatment costs. Nitrogen trapping in Difficult Run floodplains had a total estimated value of 727, 226 USD per year. Differences in floodplain nitrogen retention can be used to target areas for conservation and restoration.